Sociology and hierarchy of voids: a study of seven nearby CAVITY galaxy voids and their dynamical CosmicFlows-3 environment - Courtois, Hélène; Weygaert, R. van de; Aubert, M.; Pomarède, D.; Guinet, D.; Domínguez-Gómez, J.; Florido, E.; Galbany, L.; García-Benito, R.; Hulst, J. M. van der; Kreckel, Kathryn; Miura, R. E.; et al. (Astronomy and astrophysics, 2023)
Context. The present study addresses a key question related to our understanding of the relation between void galaxies and their environment: the relationship between luminous and dark matter in and around voids.Aims. To explore the extent to which local Universe voids are empty of matter, we study the full (dark+luminous) matter content of seven nearby cosmic voids that are fully contained within the CosmicFlows-3 volume.Methods. We obtained the matter-density profiles of seven cosmic voids using two independent methods. These were built from the galaxy redshift space two-point correlation function in conjunction with peculiar velocity gradients from the CosmicFlows-3 dataset. Results. The results are striking, because when the redshift survey is used, all voids show a radial positive gradient of galaxies, while based on the dynamical analysis, only three of these voids display a clear underdensity of matter in their center. Conclusions. This work constitutes the most detailed observational analysis of voids conducted so far, and shows that void emptiness should be derived from dynamical information. From this limited study, the Hercules void appears to be the best candidate for a local Universe pure “pristine volume”, expanding in three directions with no dark matter located in that void.